Healthcare and Disease Burden in Africa The Impact of Socioeconomic Factors on Public Health - Niohuru, Ilha (SpringerBriefs in Economics,, 2023)
This open access book evaluates African healthcare systems from multiple perspectives. By examining empirical data from various African countries, it analyzes the effects of socioeconomic factors such as urbanization, population growth, and education on various health indicators, including the situation of health professionals, patients's decision making, health resource distribution, mortality rates, and the burden of disease. Furthermore, topics such as the use of social media in healthcare and insurance policy in Africa are addressed. This book appeals to scholars and professionals interested in healthcare in Africa.